Odpowiedzi

Najlepsza Odpowiedź!
2009-12-16T18:12:29+01:00
6( m/6 - n/6)= 6*m/6-6*n/6=m-n
5*(1/5p + 1/5 g)= 5*1/5p+5*1/5g=p+g
-7(m/7-n/7-p/7+g/7+2/7)=-7*m/7-7*(-n/7)-7*(-p/7)-7*g/7+2=
-m+n+p-g-2
2 5 2
2009-12-16T18:13:47+01:00
6( m/6 - n/6)= 6*m/6-6*n/6=m-n
5*(1/5p + 1/5 g)= 5*1/5p+5*1/5g=p+g
-7(m/7-n/7-p/7+g/7+2/7)=-7*m/7-7*(-n/7)-7*(-p/7)-7*g/7+2=
-m+n+p-g-2
2009-12-16T18:34:34+01:00
6( m/6 - n/6)=6m/6 - 6n/6=m-n (po skroceniu szostek)

5*(1/5p + 1/5 g)=5/5 p +5/5 g=p+g

-7(m/7-n/7-p/7+g/7+2/7)=-7m/7-(-7n/7)-(-7p/7)+(-7g/7)+(-14/7)=-m+n+p-g-2